Super-Refractory Status Epilepticus in Children: A Retrospective Cohort Study. Issue 12 (December 2021) - Vasquez, Alejandra; Farias-Moeller, Raquel; Sánchez-Fernández, Iván; Abend, Nicholas S.; Amengual-Gual, Marta; Anderson, Anne; Arya, Ravindra; Brenton, James N.; Carpenter, Jessica L.; Chapman, Kevin; Clark, Justice; Gaillard, William D.; et al.
Abstract : OBJECTIVES: To characterize the pediatric super-refractory status epilepticus population by describing treatment variability in super-refractory status epilepticus patients and comparing relevant clinical characteristics, including outcomes, between super-refractory status epilepticus, and nonsuper-refractory status epilepticus patients. DESIGN: Retrospective cohort study with prospectively collected data between June 2011 and January 2019. SETTING: Seventeen academic hospitals in the United States. PATIENTS: We included patients 1 month to 21 years old presenting with convulsive refractory status epilepticus. We defined super-refractory status epilepticus as continuous or intermittent seizures lasting greater than or equal to 24 hours following initiation of continuous infusion and divided the cohort into super-refractory status epilepticus and nonsuper-refractory status epilepticus groups. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: We identified 281 patients (157 males) with a median age of 4.1 years (1.3–9.5 yr), including 31 super-refractory status epilepticus patients. Compared with nonsuper-refractory status epilepticus group, super-refractory status epilepticus patients had delayed initiation of first nonbenzodiazepine-antiseizure medication (149 min [55–491.5 min] vs 62 min [33.3–120.8 min]; p = 0.030) and of continuous infusion (495 min [177.5–1, 255 min] vs 150 min [90–318.5 min]; p = 0.003); prolonged seizure duration (120 hr [58–368 hr] vs 3 hr [1.4–5.9 hr]; p < 0.001) and length of ICU stay (17 d [9.5–40 d] vs [1.8–8.8 d]; p < 0.001); more medical complications (18/31 [58.1%] vs 55/250 [22.2%] patients; p < 0.001); lower return to baseline function (7/31 [22.6%] vs 182/250 [73.4%] patients; p < 0.001); and higher mortality (4/31 [12.9%] vs 5/250 [2%]; p = 0.010). Within the super-refractory status epilepticus group, status epilepticus resolution was attained with a single continuous infusion in 15 of 31 patients (48.4%), two in 10 of 31 (32.3%), and three or more in six of 31 (19.4%). Most super-refractory status epilepticus patients (30/31, 96.8%) received midazolam as first choice. About 17 of 31 patients (54.8%) received additional treatments. CONCLUSIONS: Super-refractory status epilepticus patients had delayed initiation of nonbenzodiazepine antiseizure medication treatment, higher number of medical complications and mortality, and lower return to neurologic baseline than nonsuper-refractory status epilepticus patients, although these associations were not adjusted for potential confounders. Treatment approaches following the first continuous infusion were heterogeneous, reflecting limited information to guide clinical decision-making in super-refractory status epilepticus. Abstract : Supplemental Digital Content is available in the text.